PRAKONSEPSI, MINAT DAN SIKAP MAHASISWA TERHADAP ISU-ISU KONSERVASI BIODIVERSITAS - Mike Dewi Kurniasih (Universitas Muhammadiyah Semarang, 2018)
The aim of this study was to describe the preconception, interest and attitude among undergraduate students toward biodiveristy conservation issues. This research is a descriptive research using quantitative approach. The data was collected from 100 undergraduate students of IKIP Veteran Jawa Tengah by test, questionnaire and interview sheet. Results showed that the preconception of undergraduate students toward the biodiversity conservation issue is quite good with score 75.57. This study reveals that there were some misconception about biodiversity conservation especially about the conservation strategy. Theinterest of undergraduates student toward this issues is on good category. It showed by the average score of undergraduate student’s interest that reach 84.25. Meanwhile, the undergraduate’s attitude on the biodiversity conservation is good. This indicated by It showed by the average score of undergraduate student’s attitude that reach 83,44. Keywords: Prakonsepsi, Minat, Sikap, Konservasi, Biodiversitas